2014
DOI: 10.1093/molbev/msu308
|View full text |Cite
|
Sign up to set email alerts
|

The Evolutionary History of Termites as Inferred from 66 Mitochondrial Genomes

Abstract: Termites have colonized many habitats and are among the most abundant animals in tropical ecosystems, which they modify considerably through their actions. The timing of their rise in abundance and of the dispersal events that gave rise to modern termite lineages is not well understood. To shed light on termite origins and diversification, we sequenced the mitochondrial genome of 48 termite species and combined them with 18 previously sequenced termite mitochondrial genomes for phylogenetic and molecular clock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

32
336
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(376 citation statements)
references
References 89 publications
32
336
2
2
Order By: Relevance
“…In this study, we confirmed the relationship pattern and dating of the three genera as found in earlier molecular studies [10,15,25,37]. We found that the split between Reticulitermes and Heterotermes þ Coptotermes occurred around 59 Ma (49.9 -69.5 Ma 95% CI), the most recent common ancestor of the clade Heterotermes þ Coptotermes arose 36 Ma (33.9 -40.5 Ma 95% CI), and Coptotermes split from sister Heterotermes species around 24.5 Ma (21.0 -27.8 Ma 95% CI).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we confirmed the relationship pattern and dating of the three genera as found in earlier molecular studies [10,15,25,37]. We found that the split between Reticulitermes and Heterotermes þ Coptotermes occurred around 59 Ma (49.9 -69.5 Ma 95% CI), the most recent common ancestor of the clade Heterotermes þ Coptotermes arose 36 Ma (33.9 -40.5 Ma 95% CI), and Coptotermes split from sister Heterotermes species around 24.5 Ma (21.0 -27.8 Ma 95% CI).…”
Section: Discussionsupporting
confidence: 91%
“…The original metagenomic dataset of Embiratermes neotenicus consisted of 209,047,724 raw reads, from which 269,723 mitochondrial reads were recruited and assembled into one circular contig of 15,868 bp, with an average coverage of 2418-fold, an asymmetric nucleotide composition (42.5% A, 21.6% C, 12.1% G, 23.8% T) and an overall G þ C content of 33.7 mol% (accession number KY436202). These values are consistent with the length and nucleotide composition of other higher termite mitogenomes (Bourguignon et al 2015;Dietrich & Brune 2016).…”
supporting
confidence: 88%
“…In both cases, the gene order and orientation were identical to those of other termites, which have retained the organization of the ancestral insect mitochondrial genome (Cameron 2014). Phylogenetic analysis of protein-coding sequences yielded the same tree topology for the Syntermitinae subfamily as previously reported by Bourguignon et al (2015) using partial mitochondrial genomes of Labiotermes labralis and Embiratermes neotenicus generated by PCR amplification and Illumina sequencing (Figure 1). …”
supporting
confidence: 64%
See 1 more Smart Citation
“…A particularly striking case of convergent evolution occurred within the holometabolous Hymenoptera and in the hemimetabolous termites (Isoptera), which are separated by over 350 Myr of evolution 5 . Termites evolved within the cockroaches around 150 Myr ago, towards the end of the Jurassic period 6,7 , about 50 Myr before the first bees and ants appeared 5 . Therefore, identifying the molecular mechanisms common to both origins of eusociality is crucial to understanding the fundamental signatures of these rare evolutionary transitions.…”
mentioning
confidence: 99%